The Effect of Plasma Releases on Equatorial Spread F—a Simulation Study - Zawdie, Katherine A.; Huba, Joseph D.; Dhadly, Manbharat S.; Papadopoulos, Konstantinos (Frontiers in Astronomy and Space Sciences, 2019)
A currently unfulfilled goal of active experimentalists is to control the occurrence of instabilities in the ionosphere such as Equatorial Spread F (ESF), which generates large-scale electron density depletions (plasma bubbles) in the night-time ionosphere at low latitudes. It has been theorized that by artificially injecting ionizing chemicals (such as barium) into the ionosphere, ESF may be suppressed. Large plasma releases modify the ionospheric conductance, which affects the electrodynamics of the system and may thereby influence the growth (or suppression) of ESF. In this study, the feasibility of controlling ESF growth via plasma releases in the ionosphere is examined for the first time using a fully three-dimensional, first-principles model of the ionosphere: SAMI3/ESF (Sami is Another Model of the Ionosphere). The numerical simulations show that under certain circumstances plasma injections may be able to trigger or suppress ESF growth. The results indicate that the plasma density must be above a threshold level to sufficiently modify the ionospheric conductance. In addition, the plasma must be injected at a suitable location and time. The results of this numerical investigation provide guidance for future experimental campaigns.